Negative inotropic and dromotropic actions of SiO2 nanoparticles on isolated rat hearts: Effects on Na+ and Ca2+ currents - Julio Alvarez-Collazo; Loipa Galán-Martínez; Alicia Fleites-Vazquez; Alicia Sánchez-Linde; Karel Talavera-Pérez; Julio L. Alvarez (GarVal Editorial Ltda., 2016)
Context: SiO2 nanoparticles (NP) are widely used in the industry and in varied biotechnological and medical applications. However, epidemiological studies suggest that pollution with fine particles (in which silica is an inorganic component) may increase morbidity and mortality from cardiovascular diseases, but little is known about their potential cardiovascular actions. Aims: To study the actions of SiO2 nanoparticles on the electrical and contractile activity of rat hearts and to identify the possible underlying cellular mechanisms. Methods: Surface electrogram (ECG) and force of contraction (FC) was recorded in isolated rat hearts. Na+ and Ca2+ currents (INa and ICaL, respectively) were recorded, with the patch-clamp technique, in enzymatically isolated rat ventricular cardiomyocytes. Results: SiO2 NP (1-30 µg/mL) decreased the FC and markedly increased QRS duration and QT interval in spontaneously beating hearts. Electric stimulation (RR = 400 ms) partially restored the FC. In patch-clamp experiments NP (30 µg/mL) decreased INa in a use-dependent manner and increased ICaL. Conclusions: SiO2 nanoparticles exert a negative inotropic action in rat hearts due, in part, to a decrease in the fast sodium current responsible for cardiac depolarization. SiO2 nanoparticles are also able to increase the L-type Ca2+ current. These actions should be taken into account when analyzing the toxic effects of these nanoparticles.